TRANSFORMASI DIGITAL DI PONDOK PESANTREN TRADISIONAL : STUDI KASUS DI PONDOK PESANTREN UMMUL QURO AS-SUYUTY PLAKPAK PEGANTENAN PAMEKASAN - Fahmi, Ach. Syafiq; Rosi, Rois Imron; Rofiqi (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2024)
Traditional Islamic boarding schools are now faced with the challenges of the times, where the development of information and communication technology is increasingly rapid, requiring educational institutions, including Islamic boarding schools, to transform into digitalization, but this does not mean that they have to eliminate conventional methods, but rather development that aims to keep up with the flow of globalization. and modernization. This research investigates Digital Transformation in Traditional Islamic Boarding Schools: Case Study at Ummul Quro As-Suyuty Plakpak Pegantenan Pamekasan Islamic Boarding School, which aims to explore the use and utilization of digital media in these Islamic boarding schools. By using a qualitative case study type approach, the results of this research show that the use of digital media in every activity, both inside and outside the classroom, is considered very important and helps the implementation of education. In the classroom, teachers are helped by the presence of digital media in conveying material and understanding it. students, it is also used for distance learning when there are assignments outside the boarding school, this is usually done by the kyai via WA and Zoom and then displayed on electronic TV so that learning continues as usual. Meanwhile, outside of class, digital media is used to record and immortalize every activity at the Islamic boarding school and then post it via social media, both YouTube, Instagram and Facebook.